Development and Characterization of a Novel Live Attenuated Vaccine Against Enteric Septicemia of Catfish - Abdelhamed, Hossam; Lawrence, Mark L.; Karsi, Attila (Frontiers in Microbiology, 2018)
Edwardsiella ictaluri is a Gram-negative intracellular pathogen causing enteric septicemia of channel catfish (ESC). Type six secretion system (T6SS) is a sophisticated nanomachine that delivers effector proteins into eukaryotic host cells as well as other bacteria. In the current work, we in-frame deleted the E. ictaluri evpB gene located in the T6SS operon by allelic exchange. The safety and efficacy of EiΔevpB as well as Aquavac-ESC, a commercial vaccine manufactured by Intervet/Merck Animal Health, were evaluated in channel catfish (Ictalurus punctatus) fingerlings and fry by immersion exposure. Our results showed that the EiΔevpB strain was avirulent and fully protective in catfish fingerlings. The EiΔevpB strain was also safe in catfish fry, and immersion vaccination with EiΔevpB at doses 106 and 107 CFU/ml in water resulted in 34.24% and 80.34% survival after wild-type immersion challenge compared to sham-vaccinated fry (1.79% survival). Catfish fry vaccinated with EiΔevpB at doses 106, 107, and 108 CFU/ml in water exhibited dose-dependent protection. When compared with Aquavac-ESC, EiΔevpB provided significantly higher protection in catfish fingerlings and fry (p < 0.05). Results indicate that the EiΔevpB strain is safe and can be used to protect catfish fingerlings and fry against E. ictaluri.